Role of toll-like receptors in pulmonary immunity: mechanisms and therapeutic implications - Qu, Zhuojian; Guo, Zhiliang; Yang, Chunjuan; Guan, Xiumei; Cheng, Min; Wang, Pingping; Xu, Donghua (Frontiers in Immunology, 2025)
Toll-like receptors (TLRs) belong to the family of pattern recognition receptors (PRRs), playing critical roles in linking innate with adaptive immunity by recognizing pathogen-associated molecular patterns (PAMPs) and danger-associated molecular patterns (DAMPs). TLRs and TLR signaling pathways serve as not only the first line of pulmonary defense against pathogens infection but crucial factors in maintaining pulmonary immune homeostasis. However, aberrant activation of TLR signaling leads to inflammation and immune dysregulations, contributing to various pulmonary diseases, including inflammation, infection, fibrosis, and malignancy. This review summarizes the updated roles of TLRs and TLR signaling in lung development and the establishment and regulation of pulmonary region-specific immunity. We further elucidate the involvement of TLRs and TLR signaling in the onset and progression of lung diseases, such as infections, fibrosis, malignancies, and immune disorders. It would provide updated insights into the exploration of novel diagnostic and therapeutic strategies targeting TLRs and TLR signaling in pulmonary diseases.